2021
DOI: 10.1016/j.nicl.2021.102561
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of neurodegeneration in Spinocerebellar Ataxia type 7

Abstract: Highlights DTI study reveals brain-wide differences between SCA7 patients and controls. DTI dual-compartment model controls for increased CSF-like free water in patients. Tensor-based deformations show SCA7 tissue loss extends beyond cerebellum. Focal atrophy, but global microstructural abnormalities were observed in SCA7.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…It should be noted, however, that few cerebral regions of the sensorimotor system (i.e., left paracentral lobule, right middle cingulum, right postcentral gyrus, right middle temporal pole, and right cuneus) show smaller volumes in NonP patients compared to SlowP. This result is in agreement with recent works that detected either gray matter atrophy or microstructural alterations in sensorimotor cortices, motor association areas, and temporal regions of patients with ataxia ( 19 , 23 , 36 ). Even though, since no specific studies have investigated these alterations in patients with Joubert syndrome, it is hard to infer the mechanisms underlying the different volumetric pattern that we revealed in NonP and SlowP patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It should be noted, however, that few cerebral regions of the sensorimotor system (i.e., left paracentral lobule, right middle cingulum, right postcentral gyrus, right middle temporal pole, and right cuneus) show smaller volumes in NonP patients compared to SlowP. This result is in agreement with recent works that detected either gray matter atrophy or microstructural alterations in sensorimotor cortices, motor association areas, and temporal regions of patients with ataxia ( 19 , 23 , 36 ). Even though, since no specific studies have investigated these alterations in patients with Joubert syndrome, it is hard to infer the mechanisms underlying the different volumetric pattern that we revealed in NonP and SlowP patients.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, Olivito et al ( 21 ) showed a specific pattern of WM microstructural damage resulting in a cerebro-cerebellar dysregulation associated with the neurodegenerative processes of spinocerebellar ataxia (SCA), while Friedreich ataxia patients showed a significant reduction in the number of streamlines of cerebro-cerebellar tracts, which led to secondary effects in other cortical areas, such as the supplementary motor area, cingulate and frontal cortex, and subcortical nuclei ( 22 ). Fractional Anisotropy (FA) and Mean Diffusivity (MD) maps, derived from diffusion tensor imaging (DTI), also demonstrated the degeneration of the cerebro-cerebellar loop by revealing microstructural abnormalities comparable to those found by neuropathology in SCA7 ( 23 ), and monitoring ataxia severity through alterations of the cortico-ponto-cerebellar pathway in adult-onset ataxic neurodegenerative patients ( 24 ). Furthermore, disruption of WM integrity in ataxic patients with respect to HC may be used to monitor the progression of pathology since these microstructural changes strongly correlated with clinical severity of one of the most frequent inherited cerebellar ataxias ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Atrophy of hippocampus is observed from 24 weeks, while the volume of midbrain and brain stem decreases at 30 weeks. Loss of grey matter tissue has been previously described in various brain regions in clinical SCA7, including the putamen and thalamus [ 28 ] using voxel-wise analysis. Diffusion tensor imaging has also demonstrated microstructural deficiencies in these structures [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of grey matter tissue has been previously described in various brain regions in clinical SCA7, including the putamen and thalamus [ 28 ] using voxel-wise analysis. Diffusion tensor imaging has also demonstrated microstructural deficiencies in these structures [ 28 ]. Further investigation is needed to conclude on the nature of these defects, which can be attributed to either demyelination, neuronal death, or gliosis, as shown recently in a mouse model of Alzheimer’s disease [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Olivito and colleagues (2017) showed a specific pattern of WM microstructural damage resulting in a cerebrocerebellar dysregulation associated with the neurodegenerative processes of spinocerebellar ataxia (SCA), while Friedreich ataxia patients showed a significant reduction in the number of streamlines of cerebro-cerebellar tracts, which led to secondary effects in other cortical areas, such as the supplementary motor area, cingulate and frontal cortex, and subcortical nuclei (Zalesky et al, 2014). Fractional Anisotropy (FA) and Mean Diffusivity (MD) maps, derived from diffusion tensor imaging (DTI), also demonstrated the degeneration of the cerebro-cerebellar loop by revealing microstructural abnormalities comparable to those found by neuropathology in SCA7 (Parker et al, 2021), and monitoring ataxia severity through alterations of the cortico-ponto-cerebellar pathway in adult-onset ataxic neurodegenerative patients (Kitamura et al, 2008). Furthermore, disruption of WM integrity in ataxic patients with respect to HC may be used to monitor the progression of pathology since these microstructural changes strongly correlated with clinical severity of one of the most frequent inherited cerebellar ataxias (Kang et al, 2014).…”
Section: Introductionmentioning
confidence: 90%